Evolution of the metaphor of friendship in Belarusian television programmes of the 1956–1990s: semantic, pragmatic, and syntactic levels of cognitive modelling - Morozowa, Elena I. (Journal of the Belarusian State University. Journalism, 2024)
The article substantiates the importance of discursive and historical research of Belarusian television programmes as a recorded speech experience of society. Extensive material from microphone folders and video recordings from 1956 (start of broadcasting of the Minsk studio of television) until 1991 (creation of the Belteleradiocompany) shows that domestic television communication preserves and updates in the thinking and activities of its agents a cognitive metaphor, the source of which is the concept of friendship. At the semantic level of discourse the strengthening of the connection between the cognitive metaphor of friendship and the concept of personal emotional relationships is shown. Speech techniques for embodying this tendency are highlighted at the pragmatic (the use of second person pronouns, proper names when addressing the audience, rhetorical questions, constructing the subjective position of the presenter instead of the announcer, creating a dramatic confrontation between the addresser and the addressee) and syntactic (the use of the Belarusian language in television communication, personal stories of viewers, music videos and the image of friends’ apartment in studio scenography as macrostructures of discourse) levels.